Evaluating carbon removal: Integrating technical potential with environmental, social, governance criteria, and sequestration permanence - Jan Mertens; Christian Breyer; Ronnie Belmans; Corinne Gendron; Patrice Geoffron; Carolyn Fischer; Elodie Du Fornel; Richard Lester; Kimberly A. Nicholas; Paulo Emilio V. de Miranda; Sarah Palhol; Peter Verwee; et al. (iScience)
Summary: Climate modeling suggests that achieving international climate goals requires a reduction in current CO2 emissions by over 90%, with any remaining emissions to be addressed through carbon dioxide removal (CDR) solutions. Sixteen CDR strategies are evaluated by integrating technical potential, environmental, social, and governance (ESG) criteria, along with sequestration permanence. This evaluation, conducted by ENGIE’s scientific council using an interdisciplinary Delphi panel methodology, proposes a “quality” measure for each technology. This measure combines ESG scores and sequestration timescales to rank and select the most promising solutions. The findings highlight the necessity for further research to understand and mitigate ESG impacts, aiming to inform both future research and current decision-making to support the effective and legitimate use of CDR strategies.